Using graphic productions for identification purposes, and psychological and pedagogical diagnosis - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The problem raised is important inasmuch as drawing conclusions from handwriting may, in many cases, determine aperson’s fate, which does not only involve opinion making in criminal or civil cases, but also those related to applying arelevant therapy to aperson with mental function disorders, or psychiatric and neurological disorders; to proper guidance on achild’s school career or anadult person’s professional career development; to apossibility of undertaking aparticular action, etc. It shall also be highlighted that the following reflections present Polish realities with regard to the raised problems, and they also show some controversies which arise with regard to the selected cognitive methods. The present publication is primarily addressed to practitioners, i.e. persons who – for their professional reasons – hire handwriting experts, and evaluate the opinions issued by such experts, meaning the broadly understood judicial bodies. It can also serve as a teaching aid for students attending forensic, criminal or civil procedure courses.
Keywords: pismo ręczne; badania pisma ręcznego; ekspertyza pisma ręcznego; identyfikacja osoby; ekspert; metody analizy pisma ręcznego; diagnoza psychologiczna; diagnoza pedagogiczna